Personality disorders: a dimensional approach - Gamba, Fernando (2020)
doi: 10.26439/persona2020.n023(1).4830 In the field of clinical psychology, there is a growing consensus about thedeficiencies of the categorical diagnosis system for personality disorders (PD), sinceit is insufficient to cover the dysfunctional experiences of patients. These deficiencies cause an incomplete system, since it excludes essential and idiosyncratic information necessary to better understand the patients. Moreover, this situation negatively affects the adequate conceptualization of the problems and the design of the interventions. If too many difficulties arise when implementing a diagnostic model in psychotherapy, it is possible to think that the model should be modified instead of trying to adjust psychotherapy to the model. The conceptualization of PD from the so-called “dimensional perspective” makes it possible to address the special features of each subject and, thus, improve the quality of the interventions. This work aims to explain how such dimensional perspective, which currently has a strong empirical support, can improve the clinical understanding of these disorders and their therapeutic intervention.